Respostas
respondido por:
1
Vamos lá
Delta = b² - 4ac
Delta = 9² - 4*1*0
Delta = 81
x = (-b + Vdelta) / 2a
x = (-9 + V81) / 2*1
x = (-9 + 9) / 2
x = 0 / 2
x = 0
x' = (-b - Vdelta) / 2a
x' = (-9 - V81) / 2*1
x' = (-9 - 9) / 2
x' = -18 / 2
x' = -9
Espero ter ajudado
Delta = b² - 4ac
Delta = 9² - 4*1*0
Delta = 81
x = (-b + Vdelta) / 2a
x = (-9 + V81) / 2*1
x = (-9 + 9) / 2
x = 0 / 2
x = 0
x' = (-b - Vdelta) / 2a
x' = (-9 - V81) / 2*1
x' = (-9 - 9) / 2
x' = -18 / 2
x' = -9
Espero ter ajudado
Annytamara:
Obrigado
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás